2007
DOI: 10.1038/nature05875
|View full text |Cite
|
Sign up to set email alerts
|

DNA repair is limiting for haematopoietic stem cells during ageing

Abstract: Accumulation of DNA damage leading to adult stem cell exhaustion has been proposed to be a principal mechanism of ageing. Here we address this question by taking advantage of the highly specific role of DNA ligase IV in the repair of DNA double-strand breaks by non-homologous end-joining, and by the discovery of a unique mouse strain with a hypomorphic Lig4(Y288C) mutation. The Lig4(Y288C) mouse, identified by means of a mutagenesis screening programme, is a mouse model for human LIG4 syndrome, showing immunod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
363
0
3

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 470 publications
(383 citation statements)
references
References 42 publications
17
363
0
3
Order By: Relevance
“…The phenotypic and functional alterations we highlighted in the KSL compartment of irradiated mice several weeks after exposure resemble observations reported in studies performed with aged mice and transgenic mice with DNA damage repair deficiencies [31][32][33]. To reveal possible additional similarities, we assessed stem/progenitor cells from 3-and 6-Gy irradiated mice for P-selectin cell-surface expression, genomic damage accumulation measured by c-H2AX foci, and frequency of apoptotic events.…”
Section: The Stem/progenitor Compartment Of Irradiated Mice Resemblessupporting
confidence: 64%
“…The phenotypic and functional alterations we highlighted in the KSL compartment of irradiated mice several weeks after exposure resemble observations reported in studies performed with aged mice and transgenic mice with DNA damage repair deficiencies [31][32][33]. To reveal possible additional similarities, we assessed stem/progenitor cells from 3-and 6-Gy irradiated mice for P-selectin cell-surface expression, genomic damage accumulation measured by c-H2AX foci, and frequency of apoptotic events.…”
Section: The Stem/progenitor Compartment Of Irradiated Mice Resemblessupporting
confidence: 64%
“…Mice with defective NHEJ have also revealed the importance of this repair pathway in hematopoietic stem cells as a key determinant in their maintenance and indicate that DNA damage accumulation may be a limiting factor for stem cell renewal (Nijnik et al, 2007;Rossi et al, 2007). Collectively, these mouse models further underscore the critical importance of the DNA DSB repair pathways during mammalian development, and highlight the utility of the mouse as an important biological system for furthering our understanding of DNA repair.…”
Section: Animal Models Of Nhej and Hr Deficienciesmentioning
confidence: 90%
“…Defects in hematopoietic stem cell (HSC) function were also described in Fancd1, Msh2, and Rad50-deficient mice (Morales et al, 2005;Navarro et al, 2006;Reese et al, 2003). In other recent experiments, Ninjik et al (Nijnik et al, 2007) and Rossi et al (Rossi et al, 2007), examining various DNA repair or telomerase-deficient mouse strains (Lig4, Ku80, Xpd, and mTR), showed that hematopoietic stem cells declined rapidly in functionality with age, if not in number. Moreover, transplantation of mutant HSCs into normal recipient mice resulted in greatly decreased reconstitutive ability in their hosts compared to HSCs derived from normal mice.…”
Section: How Does the Dna Damage Response Affect Tissue Homeostasis?mentioning
confidence: 98%